Pengaruh Kinerja Keuangan Perusahaan Terhadap Return Saham Pada Perusahaan Sektor Makanan dan Minuman Di PT Bursa Efek Indonesia - Elly Salim; Isnurhadi Isnurhadi (JURNAL MANAJEMEN DAN BISNIS SRIWIJAYA, 2011)
This research is conducted to obtain the influence financial performance indicators; Return On Equity, Debt to Equity Ratio, Dividend Payout Ratio, Return On Assets, and Earning Per Share  to the stock return of foods and beverage sector at Indonesian Stock Exchange..The sample used in this research is purposive sampling. There have been 15 samples taken from companies listing in Indonesia Stock Exchange. The data used in this study are secondary collected from financial statements.By using 95% of confidence level, it was found that Return On Equity, Debt to Equity Ratio, Dividend Payout Ratio, Return On Assets, and Earning Per Share  significantly affect stock return. For further research, it is axpected to add some new variables effecting stock return.Keyword : Return On Equity, Debt to Equity Ratio. Dividend Payout Ratio, Return On Assets, Earning Per Share, Stock return